Семейная медицина сегодня и проблема ее дальнейшей интеллектуализации с помощью информационных технологий и компьютерных систем - Кузьмина, К. И.; Оноприенко, Валерий Николаевич; Козак, Николай Саввич; Семик, Татьяна Михайловна; Андон, Татьяна Андреевна (НТУ "ХПИ", 2012)
This paper discusses the problems of using modern technologies and computer systems in order to create highly intelligent information biotechnologies, in particular during implementation of innovation program "Family Medicine". The paper discusses in detail the basic knowledge about the structure of personality, its adaptive interdisciplinary sociopsychophysiological portrait and individual adaptive-information space (IAIS) possessing high level of comfort and adequacy of human genetic organization.
Keywords: адаптационно-информационное пространство; семейная медицина; отношение к семье; принцип превентивности